Answer:
- [ A/[A/nB]^1/1-n + B/ [A/nB]^n/1-n].
Step-by-step explanation:
The mathematical representation for the net potential energy as described in the Question above is given below as;
En = -A/r + B/r^n.
Therefore, let's call the equation above equation (1). Hence, there is the need to differentiate equation (1) above wrt r.
(NB: wrt = with respect to)
Thus, [dEn/ dr] = 0. -------------------------(2).
d [ - A/r + B/r^n]/ dr = 0. -------------------(3).
A/r^2 - nB/r^n+1 = 0 ------------------------(4).
r^2/r^n+1 = A/nB ----------------------------(5).
r^1-n = A/nB -----------------------------------(6).
(1 - n )ln r= ln A/nB ------------------------(7)
ln r = 1/1 - n ln [A/nB] ---------------------(8).
r = e^ln(A/nB)^1/1-n ----------------------(9).
r = [A/nB]^1/1-n. ---------------------------(10).
Thus, put the value in (10) above that is r = [A/nB]^1/1-n into equation (1).
Hence, the bonding energy = - [ A/[A/nB]^1/1-n + B/ [A/nB]^n/1-n].